Basic life support knowledge among nurses at public health center in rural Banten Province, Indonesia - Priyo Sasmito; Mikawati Mikawati; Fika Indah Prasetya; Yetti Syafridawita; Nunuk Sri Purwanti; Yuyun Tafwidhah; Mochamad Budi Santoso; Nisa Arifani (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Public Health Center (PHC) is one of the primary healthcare facilities that has an important role in the chain of survival of out-of-hospital cardiac arrest (OHCA) patients, especially in rural areas. Nurses are an important component of health workers in PHC. Basic Life Support (BLS) knowledgeis the basic component of building a qualified resuscitation.Purpose: To analyze the relationship between demographic characteristics of PHC’s nurses in a rural area and their knowledge about BLS.Method: An observational analytical study with a cross-sectional approach involved 32 PHC nurses with total sampling techniques. The data was analyzed with the Spearman Rho and Fisher Exact test.Results: 32 nurses were involved. Most respondents are male (18/56.25%), have a Diploma educational background (23/71.88%), and non-government employees (24/75%). The average age of respondents was 34.75 years, and the average worked for 9.25 years. The level of knowledge of BLS was mostly more than 56% (25/78.1%). The knowledge average was 74.06+ 8.93 with a median of 75 anda score range of 50-85. Gender, educational background, BLS certificate upgrades, and employment status were not related to the level of knowledge of BLS. Age and length of work variables have a significant correlation with knowledge. Calculated rs was -0.043 with a p-value of 0.008 (α 0.05) for age and rs value of -0.353 with a p-value of 0.024 (α 0.05) for length of work.Conclusion: Gender, educational background, BLS certificate upgrades, and employment status were not related to the level of knowledge of BLS.There is a sufficient and significant relationship between the age and length of workwith knowledge of BLS with the opposite direction of the relationship.The older and longer a nurseworks, the lowerthe nurse’s knowledge of BLS. Routine BLS training sessions or emergency drills in PHC both online and offline can be some solution in partnership with emergency organizations and nearby referral hospitals.